MODEL FOR HANDLING DISADVANTAGED VILLAGE IN FACING THE VICIOUS CIRCLES OF POVERTY IN SITUBONDO DISTRICT (CASE STUDY IN BESUKI VILLAGE) - Tria Apriliana; Irena Paramita Pramono (UNEJ e-Proceeding)
The main problem of concern in economic development studies so far is the question of poverty. The effectiveness of poverty alleviation programs that have been piloted by both top-down and bottom-up government are not running well yet. Small and Medium Enterprises (SMEs) become one of the sectors that dominate economic activity besides agriculture sector. The purpose of this research was to obtain the synergy model of the policy implementation of underdeveloped village to face the vicious circles of poverty. Besides, this research was aimed to obtain a relationship model of factors of success in the implementation of disadvantaged village policy in facing the vicious circles trap. The data were processed and analyzed using SWOT and institutional analysis through focus group discussion (FGD) technique with the stakeholders. The results of the analysis showed that in enhancing economic activities through SMEs, an active role of government is needed as a mediator that connects SMEs with stakeholders such as academics, financial institutions, and trade associations.